2016
DOI: 10.1002/2015jc011053
|View full text |Cite
|
Sign up to set email alerts
|

Moored observation of abyssal flow and temperature near a hydrothermal vent on the Southwest Indian Ridge

Abstract: Four moorings were deployed near “Dragon Flag,” an active hydrothermal vent in the valley of the Southwest Indian Ridge. The goal was to examine the variability of currents and temperature, which will guide the trajectory of spreading plumes. The mean current was cross‐isobath, and the circulation was characterized by a submesoscale circulation. Observed currents also showed fluctuations with periods of 1–15 days. The inferred phase speed and wavelength for the wave with a period of 4.4 day are 10.4 km d−1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…For example, reversal currents are observed in the Kane Gap connecting deep basins in the Equatorial Atlantic 9 . Similar variability at synoptic time scales is found in the abyssal layer of the Northeast Pacific 11 and Southwest Indian Ocean 40 . Repeated moorings deployed in the Vema Channel since 1979 28 do not show significant long-term trends in the abyssal velocity.…”
Section: Discussionsupporting
confidence: 71%
“…For example, reversal currents are observed in the Kane Gap connecting deep basins in the Equatorial Atlantic 9 . Similar variability at synoptic time scales is found in the abyssal layer of the Northeast Pacific 11 and Southwest Indian Ocean 40 . Repeated moorings deployed in the Vema Channel since 1979 28 do not show significant long-term trends in the abyssal velocity.…”
Section: Discussionsupporting
confidence: 71%
“…Another possible reason may be the currents in the studied area that are quite fast and prohibit the aggregation and deposition of colloids and particles. It has been observed that the current velocity was over 6 cm/s with the maximal value of 19.1 cm/s near the Longqi field (Liao et al ).…”
Section: Resultsmentioning
confidence: 99%
“…The possible sources include diffuse flow adjacent to the high-temperature vents and/or in situ biological activities. Since the Longqi hydrothermal field was found in 2007 (Tao et al, 2012), various studies, including the physical, chemical, and biological characteristics of the hydrothermal fluids, plumes, and the diffuse flow, have been carried out (Ji et al, 2017;Li et al, 2014Li et al, , 2016Liao et al, 2016;Pan et al, 2016;Peng et al, 2011;Tao et al, 2012Tao et al, , 2014Wang et al, 2012Wang et al, , 2015. It was found that there were no significant differences in microbial compositions between the hydrothermal plume samples and the ambient seawater (Li et al, 2016).…”
Section: The Fe Speciationmentioning
confidence: 99%
“…Theoretical studies have demonstrated that the presence of sloping topography can derive bottom‐trapped topographic Rossby waves (TRWs; Rhines, ). TRWs have been observed by field measurements in different ocean basins (e.g., Hamilton, , , ; Hogg, , ; Kolodziejczyk et al, ; Liao et al, ; Louis et al, ; Pickart, ; Shu et al, ; Timmermans et al, ; Zhao & Timmermans, ). In these measurements, the vertical structure and variability of deep current and/or isotherm displacement conform to TRW theories of intensification with depth and highly vertical coherence throughout the deep‐water column.…”
Section: Introductionmentioning
confidence: 98%